Biocontrol Dynamicsttrichogramma SPP Associated With Helicoverpa Armigera (Hubner) In Ethiopian Mixed Vegetation Ecosystems - Tulu, Mulugeta Negeri (2005)
The natural occurrence of egg parasitoids was assessed by investigating the compatibility of Trichogramma spp. associated with the African bollworm, Helicoverpa armigera (Hiibner) under mixed vegetation ecosystems. Field and laboratory investigations were conducted to study the diversity, species composition, biology and effectiveness of recovered Trichogramma spp. and other egg parasitoids on H. armigera. Assessments on the diversity of egg parasitoids conducted on farmers' fields on 50 randomly selected sites from four contrasting agro-ecosystems indicated that there were four main groups of Hymenopteran egg parasitoids. They were the two Telenomus spp. (Scelionidae), two Trichogrammatoidea spp. nr. lutea and nr armigera (Trichogrammatidea), two Trichogramma spp. nr. mwanzia and nr. bournieri (Trichogrammatidae) and lastly a number of unidentified species. The natural field parasitism was estimated to be 33%; parasitism of the recovered egg parasitoid species according to locations varied from 27 to 40% while that of different crops (cotton, tomato and pepper) varied from 25 to 57%. Among those recovered from the surveyed agro-ecological locations, Trichogramma sp. nr. bournieri was recovered on various canopy structures of cotton, tomato and maize, indicating that it has a broader niche. Egg parasitoid abundance and species composition analyzed by the Czekanowski coefficient and Shannon index indicated that Tsp. nr. bournieri, Telenomus sp. and Tsp. nr. mwanzia were widespread in both low (Afar) and high altitude (Guder) agro-ecologies. The abundance of H. armigera egg and its egg parasitoids in two benchmark sites at extreme altitudes (740 and 2034 meter above sea level) during the main and offseasons on eight crop types varied with respect to crop type, season and altitude. In general, parasitism was higher during the main season. At lower altitudes, the highest count of parasitized eggs was from pigeon peas where the parasitoid Telenomus sp. was the most abundant. At higher altitudes, the highest number of parasitized eggs was recorded from tomato. The first appearance of targeted host egg during the offseason at lower altitude was in November and it was the highest number recorded. At Guder, (high altitude) during the off-season, H armigera eggs and their parasitoids were recorded from November to January in tomatoes and pigeon peas with the highest parasitism recorded in January in both crops. Observations revealed that male Tsp. nr. bournieri emerged 7-12 minutes earlier than the females. The males stood guard around the parasitized eggs awaiting the emerging female for copulation. The overall frequency distribution of the number of adults emerged daily was positively skewed for both sexes. The duration of immature and adult stages for T.sp. nr. bournieri was 9.25 and 3 days, respectively, whereas for Tsp. nr. mwanzia it was 9.35 and 2.35 days, respectively. tllPUET'AKAAN SULTAN ABDUL UNIVERSITI WTRA MALkYSlA Suitability and acceptability of H. armigera egg for ovipostion of the native Tsp. nr. bournieri, Tsp. nr. mwanzia and a Telenomus sp. was studied under laboratory conditions. Telenomus sp. failed to perform when held under laboratory conditions. The reason for this is not clear. The acceptability and suitability level .by the two Trichogramma parasitoids varied with age and density of H. armigera eggs. In general, severity of parasitism decreased with increasing host egg age while searching or foraging increased with increasing host egg age. Functional responses studied on various factitious host egg densities exposed to different numbers and combinations of parasitoid species showed the mean rate of parasitism was highest when the host eggs were exposed to an individual species of multiple females of four to eight. The mean parasitism rate increased with increasing number of adults. The host egg parasitism by Tsp. nr. bournieri and Zsp. nr. mwanzia was highly affected at temperature intervals between 10 and 40°C. The number of adult female progeny was greater than the males at different level of temperature. Trichogramma sp. nr. bournieri had a wider spectrum and its optimum temperature was between 10 and 35°C. The high efficiency of parasitism by Tsp. nr. bournieri and its superior searching capacity, as revealed by studies done under the controlled conditions of the greenhouse (under cloth mesh cage) and lathehouse (under open air cage) led to the conclussion that it was potentially promising to be exploited as a biocontrol agent against H. armigera.